The Effect Competency, Compensation And Innovation on Job Satisfaction And Employee Performance In Regional Device Organizations In Mamuju - Sulkarnain, Tri (Jurnal Ilmiah Manajemen & Kewirausahaan, 2022)
The purpose of this study is to examine and analyze empirically the effect of competence, compensation and organizational innovation on employee performance; and competence, compensation and organizational innovation on employee performance through job satisfaction. The design of this study used a survey method with cross-sectional data collection through questionnaires. Determination of the sample using simple random sampling with the number of respondents 288 employees in regional organizations in Mamuju Regency. The analytical method used in testing the hypothesis is Structural Equation Modeling (SEM) with Amos. The results of the study provide evidence that competence has a positive and significant effect on employee job satisfaction; compensation has a positive and significant effect on employee job satisfaction; organizational innovation has a positive and significant effect on employee job satisfaction; competence has a positive and significant effect on employee performance; compensation has a positive and significant effect on employee performance; organizational innovation has a positive and insignificant effect on employee performance; competence has a positive and significant effect on employee performance through job satisfaction; compensation has a positive and significant effect on employee performance through job satisfaction; organizational innovation has a positive and significant effect on employee performance through job satisfaction.